2013
DOI: 10.1590/s1809-98232013000100012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the practice of physical activity on the quality of life, muscle strength, balance, and physical ability in the elderly

Abstract: INTRODUCTION: Ageing has become a huge public health challenge due to the need to find solutions for improving quality of life. OBJECTIVE: This study aimed to assess quality of life, muscle strength, balance and physical capacity among elderly practitioners and non-practitioners of physical activity. MATERIALS AND METHODS: An observational, cross-sectional study was carried out involving 74 elderly individuals in the city of Santos (state of São Paulo, Brazil), divided into two groups: practitioners and non-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
1
0
5
Order By: Relevance
“…Idosos que foram submetidos a exercícios físicos regulares e programados apresentaram melhora da percepção da QV [18][19][20][21]23]. No entanto, não foi verificado se estes idosos eram ativos, sem necessariamente praticarem uma atividade física sistematizada e regular, antes da intervenção.…”
Section: Idosasunclassified
“…Idosos que foram submetidos a exercícios físicos regulares e programados apresentaram melhora da percepção da QV [18][19][20][21]23]. No entanto, não foi verificado se estes idosos eram ativos, sem necessariamente praticarem uma atividade física sistematizada e regular, antes da intervenção.…”
Section: Idosasunclassified
“…Studies have demonstrated (10)(11)(12) that more physically active people -whether older, middle-aged, or young adults -had better results in balance parameters than less active ones. In contrast, other authors (13) assessed a sample of 75 healthy individuals but did not find the same association.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos demonstraram (10)(11)(12) que pessoas com níveis mais altos de atividade física apresentaram melhores resultados nos parâmetros do equilíbrio analisados, quando comparados com indivíduos com níveis mais baixos, tanto em idosos, quanto em adultos jovens ou de meia idade. No entanto, outros autores (13) , avaliando uma amostra de 75 indivíduos saudáveis, não encontraram essa mesma associação.…”
Section: Introductionunclassified